Arlo Smith for Attorney General Press Conference - Watkins, Howard::::::::: (1989)
Back view of media cameraman showing seated: Arlo Smith speaking, Tom Bohigian, Judy Soley and ?; Standing: ?, ?, ? Robert Perez, Holley Perez and Howard Watkin s